beDNA : un projet visant à la collection systématique d’échantillons humains archéologiques à vocation paléogénétique – une première expérimentation - Pauline Ehrhardt; Philippe Chambon; Eric Gimel; Evelyne Heyer; Sophie Lafosse; Pascal Sellier; Aline Thomas; Céline Bon (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Palaeogenetics is becoming increasingly important in tackling archaeological issues. However, analyses of ancient DNA can be hampered or even prevented by the state of preservation of samples due to poor storage conditions, and because of contamination by modern DNA. The beDNA project for a national archaeological genetic data and sample bank (banque d’échantillons et de Données Nationale Archéogénétique) is developing the means to enable future palaeogenetic analyses by systematically storing human skeletal samples, with the constraints inherent to the preservation of ancient DNA taken into account. This project comprises (1) a systematic protocol for "clean" sampling of human remains to be common to all archaeological operations, (2) a dedicated storage space for samples, suited to aDNA preservation, (3) a database linking sites with the samples stored in the bank, (4) approval of sample analysis requests by authorities, after expert review. The test phase of the project, which began in September 2020 in the Île-de-France region, enabled us to evaluate and adjust both the sampling protocol in the field and the transfer process to the beDNA bank. This note describes the different stages envisaged for each sample, from the archaeological field to the genetics laboratory, as well as the development of the experimental phase and initial feedback from it.